Measures of dynamic balance under passive vertical excitation. Issue 20 (2015) - Evans, Neil D.; Zivanovic, Stana; Caprani, Colin; Barons, Martine J.
Abstract: Preliminary results are presented regarding measurement of the effect of a lively, excitable bridge structure on balance control during walking. The structure has been design to be excitable by natural walking and leads to vertical forcing on the subject in a feedback loop induced by the subject's walking. Results suggest that control in the saggital plane is primarily affected, and that this may involve an interplay between ankle and knee control. However, lateral control is strongly affected by walking frequency, which may obscure any effects of the surface.